OCCUPY WALL STREET VS. RHETORIC OF FEAR - Campos Vargas, Henry (2014)
The response of Obama´s Administration to Occupy Wall Street movement is an instanceof institutional rhetoric of fear. For this reason, this paper offers a rhetorical approachof some of texts used by Occupy Wall Street and the interaction of this movement andAmerican Government.